Tanggung Jawab Perantara Jasa Properti Kepada Konsumen Ketika Pengembang Wanprestasi - Yerico Agustinus Budyanto; Celina Tri Siwi K.; Hermanto Silalahi (Comprehensive Law Journal, 2024)
This research aims to find out how the sale and purchase agreement is implemented and legal protection, as well as the sale and purchase responsibilities carried out by the Intermediary Company PT XMarks Grande Malang in protecting consumers if the developer defaults. This research is to provide insight and new literature to future readers and writers. This research is a type of research that refers to several legal regulations in the Civil Code, Minister of Trade Regulations, and uses several legal theories to conduct research. This research was conducted using empirical juridical methods by conducting interviews with sources and to obtain as much data as possible regarding problems previously experienced by agents from PT XMarks Grande Malang. The research results show that the legal protection and responsibility of PT However, the lack of good faith on the part of one of the parties makes the problem bigger and is brought to court to resolve the problem.